ALGUNS INDICADORES DE SUSTENTABILIDADE PARA OS PEQUENOS E MÉDIOS PRODUTORES RURAIS DO MUNICÍPIO DE JAQUIRANA - Albé, Maristela de Quadros (Revista Liberato, 2013)
This dissertation aims to present sustainability proposals for medium and small rural properties in Jaquirana country (RS). Indicators were determined for the productive or economical capacity, environmental integrity, social health or life quality and cultural identity from all the sampled rural propriators. Aiming such an elaboration, it was considered the property size, family income and the local ecosystem.